Towards an explicit national health benefit package for Malaysia: a participatory multi-method study into stakeholder perspectives and evidence-informed policy design - Khairil Idham Ismail; Erni Zurina Romli; Hanin Farhana Kamaruzaman; Ku Nurhasni Ku Abd Rahim; Tengku Noor Farhana Tengku Khalid; Roza Sarimin; Syaharatul Patimah Kamarudin; Ahmad Faris Abdul Fatah; Nur Dalilah Mohd Rani; Izzuna Mudla Mohamed Ghazali (BMC Health Services Research, 2026)
Abstract Background Universal Health Coverage (UHC) is a global imperative to ensure equitable access and financial protection. While many nations utilize health benefit packages (HBPs) to define these entitlements, the transition from implicit to explicit prioritization remains a significant policy challenge. This study explored the perspectives of Malaysian healthcare stakeholders regarding the potential architecture, guiding principles, and operational modalities of an explicit National HBP (NHBP) within the context of national health reform. Methods We employed a participatory, multi-method qualitative design utilizing a modified Policy Delphi framework inspired by Evidence-Informed Deliberative Processes (EDPs). The study was executed in two phases: (1) semi-structured key informant interviews ( n = 7) to identify core system bottlenecks, followed by (2) a dual-arm Policy Delphi workshop ( n = 84) integrating baseline evidence briefs with deliberative foresight tools. To enhance deliberative rigour, specialized techniques including Problem Mapping, Futures Wheel, and Fishbowl discussions were utilized. Data were analysed using a thematic triangulation approach to ensure the inclusivity and robustness of the resulting framework. Results Triangulation revealed seven interdependent system domains essential for NHBP implementation: a robust governance model, a sustainable financing architecture, the central role of health technology assessment (HTA), a phased implementation pace, an equity-centred approach, a defined system scope and a transparent framework with legal anchoring. Furthermore, nine priority-setting criteria were identified: clinical effectiveness, cost-effectiveness, safety, budget impact, feasibility, strategic alignment, equity, burden of disease, and social acceptability. Stakeholders emphasized that an explicit NHBP must transcend technocratic design, requiring social legitimacy and statutory protection to be sustainable. Conclusions This study presents a stakeholder-driven, evidence-informed framework and implementation roadmap for an explicit NHBP in Malaysia, moving beyond traditional top-down policy design. By utilizing deliberative foresight techniques, the research offers an actionable roadmap that aligns Malaysia’s UHC journey with systemic reform priorities.